Plyometric stair jump and reaction box jump towards the leg muscles explosive power and straight-head kick frequency of pencak silat athletes - I Wayan Sumadita; I Ketut Sudiana; I Ketut Iwan Swadesi (Universitas Sriwijaya, 2023)
This study aimed at determining; 1) the different effects of leg muscle explosive power and straight-ahead kick frequency towards Pencak Silat athletes who participate in plyometric stair jump training and reaction box jump training at SMI Bali, 2) the different effects of leg muscle explosive power of Pencak Silat athletes participating in plyometric stair jump training with the athletes participating in reaction box jump training at SMI Bali, 3) the different effects of straight-ahead of Pencak athletes participating in plyometric stair jump training with the athletes participating in reaction box jump training at SMI Bali. A quasi-experimental was used as the research design of this study by adapting a non-randomized control group pretest-posttest model. The sample of this study was 45 athletes. Pre-test and post-test were used as the technique of data collection which was conducted by using a standing broad jump test as a research instrument. The collected data were analyzed quantitatively by using One-Way MANOVA. The findings indicated that: 1) there was a significant difference between the effect of leg muscle explosive power and straight-ahead kick frequency towards Pencak Silat athletes who participated in plyometric stair jump training and reaction box jump training at SMI Bali indicated by its significance value (0.000) which was less than 0.05. 2) there was a different effect of leg muscle explosive power of Pencak Silat athletes participating in plyometric stair jump training with the athletes participating in reaction box jump training at SMI Bali shown by a significant value of 0.000 which was less than 0.005, 3) there was a different effect of straight-ahead of Pencak athletes participating in plyometric stair jump training with the athletes participating in reaction box jump training at SMI Bali with a significant value 0.000 which was less than 0.005